2007
DOI: 10.1002/chem.200700875
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic and Magnetic Properties of a New Class of Cluster‐Bearing [L2Cu44‐O)(μ2‐carboxylato)4] Soft Materials

Abstract: A general approach toward amphiphilic systems bearing multimetallic clusters and their ability to form Langmuir-Blodgett films is presented. The synthetic strategy to stabilize these clusters involves the use of a ligand (HL) containing an N(2)O-donor set and long octadecanoic chains to obtain the carboxylate-supported [L(2)Cu(4)(mu(4)-O)(mu(2)-OAc)(4)]EtOH (1) and [L(2)Cu(4)(mu(4)-O)(mu(2)-OBz)(4)] (2) in which OAc(-) and OBz(-) represent acetate (1) and benzoate (2) co-ligands. These species were thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…Overall, the C 16 species start organizing at lower area per molecule values and collapse at slightly lower pressures than their C 18 counterparts, which thus reflects the influence of the chain length. In contrast to 1 and 4, species 2 and 5 display similar A c values of [26][27][28] 2 at collapse, with 5 showing a steeper slope. The reported collapse pressures for 1, 2, 4, and 5 are significantly greater than those observed for other metal-surfactant complexes.…”
mentioning
confidence: 48%
See 1 more Smart Citation
“…Overall, the C 16 species start organizing at lower area per molecule values and collapse at slightly lower pressures than their C 18 counterparts, which thus reflects the influence of the chain length. In contrast to 1 and 4, species 2 and 5 display similar A c values of [26][27][28] 2 at collapse, with 5 showing a steeper slope. The reported collapse pressures for 1, 2, 4, and 5 are significantly greater than those observed for other metal-surfactant complexes.…”
mentioning
confidence: 48%
“…We have demonstrated the feasibility of Langmuir-Blodgett (LB) films with magnetic copper(II) clusters, [27] the redox-state control and dependence of a collapse mechanism on cobalt(II) films, [28] and the factor that determines the delicate equilibrium between redox activity and amphiphilicity in copper/phenoxyl species. [29] Herein, we present an in-depth investigation of the properties of novel single-tail cationic copper(II)-containing surfactants with the ligands L PyC 18 , L PyC 16 , L PyC 14 , and L PyC 10 , in which Py = pyridine and C n indicates the alkyl chain length.…”
Section: CL 2 a C H T U N G T R E N N U N G (L Pyc 14 )] (3) [Cu mentioning
confidence: 99%
“…Inspection of geometrical data in 1a allows to observe a fair trend of shorter Cu\Cu distances associated with a narrower Cu\O(oxo)\Cu angle for the bridged metals. A search in CCDC on structurally characterized complexes with a Cu 4 (O) core with compartmental phenolate ligands bridged by four carboxylate fragments (acetate, benzoate, trifluoroacetato) retrieved thirteen structures and in the majority of these [14][15][16][17] the carboxylates assume an arrangement similar to complex 1a, and only in three cases [17][18][19] was observed a configuration analogous to that of 1. As a matter of completeness, one structure with benzoate bridging ligands shows an additional diastereomer, with three carboxylates pointing towards the same copper ion, thus having a distorted octahedral coordination sphere.…”
mentioning
confidence: 93%
“…Nevertheless, the small body of work available on the isolation and air/water interface behavior of metallosurfactant precursors still poses a major drawback to the approach. [13,14] At the forefront of this area, our group has focused on synthetic, modeling, and surface protocols involving the incorporation of magnetic µ-oxo-Cu 4 clusters in LangmuirBlodgett films, [15,16] the observation of distinctive collapse mechanisms on cobalt(II) films, [17] and the design of redoxactive copper-containing amphiphiles. [18,19] In a series of studies with iron(III), [20] cobalt(II/III), [21] and gallium-(III) [22] we have demonstrated that structural and electronic effects can determine the preferential geometry of redoxactive asymmetric NNЈO ligands in [ML 2 ] metallosurfactants.…”
Section: Introductionmentioning
confidence: 99%